A retrospective study of the prescribing and outcomes of tyrosine kinase inhibitors in chronic myeloid leukaemia over a period of more than 10 years. (10th April 2015) - Lang, A.‐S.; Mounier, M.; Roques, M.; Chretien, M. L.; Boulin, M.
Summary What is known and objective Since their introduction, tyrosine kinase inhibitors (TKIs) have been increasingly used in clinical practice. We describe the prescribing and the clinical and biological consequences of two such inhibitors, imatinib and erlotinib, in patients with chronic myeloid leukaemia (CML) in a practice setting over a period of more than 10 years. Methods All patients who received at least one TKI for chronic phase CML between 2001 and 2012 in our university hospital were included in the study. Results and discussion Of the 139 patients, with a median age of 57 years, who were surveyed, imatinib and nilotinib were prescribed as the first TKI in 131 (94%) and 8 (6%) patients, respectively. With a median follow‐up of 6 years, 342 treatment modifications were observed: 113 (33%) increased doses, 109 (32%) decreased doses, 89 (26%) TKI changes, 14 (4%) definitive discontinuations, 13 (4%) temporary discontinuations and 4 (1%) additions of IFN‐α. The main reasons for the 342 treatment modifications were adverse events (n = 112, 33%), long‐term optimal response (n = 58, 17%) and failure (n = 57, 17%). Eighty‐five (61%), 31 (22%), 18 (13%) and 5 (4%) patients had no, 1, 2 and 3 TKI changes, respectively. Imatinib was the most prescribed TKI (75%). Adverse events resulting in treatment modifications occurred in 18% of patients for imatinib, 49% for nilotinib and 41% for dasatinib (P < 0·001). Median time to TKI change whatever the reason was >50 months (not achieved) for imatinib, 22 months for nilotinib and 27 months for dasatinib (log‐rank test, P < 0·001). What is new and conclusion Imatinib was the most prescribed TKI both in the first and in subsequent therapeutic lines for chronic phase CML. Our study showed a very good efficacy–safety profile for imatinib at a median follow‐up of 6 years in an unselected French population.